2014
DOI: 10.5539/ijbm.v9n6p43
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Influence of Organizational Structure Types and Management Levels on Knowledge Management Practices in Organizations

Abstract: The purpose of this study was to investigate the difference between organizational structure types, and management levels, in terms of perceived levels of knowledge management practices within organizations. Data were collected from a sample of 155 individuals employed in San Diego County by way of a web-based survey, and were analyzed using analysis of variance (ANOVA). The results of the study indicate that the knowledge management practices of knowledge transfer, information filtering, and knowledge culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
0
15
0
7
Order By: Relevance
“…Less enactment of separation involves “less restricted spatio-temporal norms such as open-door policies” or multitasking in the workplace (Ballard & Seibold, 2003, p. 387). Immigrant workers from monochronic or middle orientation may be used to such a work environment, especially if they have jobs in information technology (IT) or the entertainment industry, which tend to have flatter organizational structures and informal cultures (Morgan, 2015; Steiger, Hammou, & Galib, 2014). In the assimilated group, immigrants who reported they adopted American cultural norms reported lower enactment of separation if they were from polychronic culture.…”
Section: Discussionmentioning
confidence: 99%
“…Less enactment of separation involves “less restricted spatio-temporal norms such as open-door policies” or multitasking in the workplace (Ballard & Seibold, 2003, p. 387). Immigrant workers from monochronic or middle orientation may be used to such a work environment, especially if they have jobs in information technology (IT) or the entertainment industry, which tend to have flatter organizational structures and informal cultures (Morgan, 2015; Steiger, Hammou, & Galib, 2014). In the assimilated group, immigrants who reported they adopted American cultural norms reported lower enactment of separation if they were from polychronic culture.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the organizational structure in fostering the learning process is evidenced in the empirical contributions of Martínez-León andMartínez-García (2011), Hao et al (2012) and Steiger (2013). The work of Martínez-León and Martínez-García (2011) sought to determine the type of structure that provides adequate conditions for the development of organizational learning The results showed that when the characteristics of the organizational structure are closer to the organic model, the levels of learning tend to be reinforced.…”
Section: Organizational Structure and Organizatio-nal Learning: Theoretical And Empirical Contri-butionsmentioning
confidence: 99%
“…Among the conclusions, the authors reinforce that the organizational structure has more effects on organizational learning than on innovation: that is, organizational learning leads to superior performance since it promotes the innovation process. Steiger (2013) in his doctoral thesis aimed to investigate the difference between the types of organizational structure on knowledge management practices within organizations. The results obtained demonstrate that the practices of knowledge transfer and information filtering are influenced by the organizational structure.…”
Section: Organizational Structure and Organizatio-nal Learning: Theoretical And Empirical Contri-butionsmentioning
confidence: 99%
“…The matrix organization structure along with the project management structure was implemented at a company at Los Angeles (Kuprenas, 2003) which was necessary for such an organization. The lack of standardization of skills is the organizational challenge in implementing the matrix organization (Steiger et al, 2014). There is a requirement to study the project team characteristics, project lead characteristics, environmental characteristics and project effectiveness (Ford & Randolph, 1992).…”
Section: Review Of Literaturementioning
confidence: 99%